The information support of the logistic system of medicine supply - I. S. Ivanchuk; A. V. Kostrov; M. A. Kostrova; V. F. Kornyushko (Тонкие химические технологии)
The primary goal of the state program "Development of Pharmaceutical and Medical industry" for 2013-2020" is the creation of innovative Russian pharmaceutical and medical industry of international standard. According to forecasts the share of Russian pharmaceutical companies in the market is going to increase from 14 to 50%. In order to ensure a complex approach to problem solving in pharmaceutical industry it needs to develop new mechanisms to manage industry sectors, clusters and enterprises. One of the most effective forms of management in this case is the creation of logistic schemes for medicine delivery to the population. The article describes the requirements for medicine delivery. We provide the economic and statistical technique – based on ABC/VEN-analysis – for the identification of the medicine demand in a large health care facility. The article uncovers the specifics of formation of a decision-making support system in time and amount of order in the context of (s, Q)-policy. The results reflect the specific features of construction of information support systems in medicine delivery.